PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL IDEAL PROBLEM SOLVING UNTUK MENINGKATKAN PEMECAHAN MASALAH PADA MATERI FLUIDA STATIS - Nindyana, Umira; Fakhruddin Z, Fakhruddin Z; Sahal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aims to produce of IDEAL problem solving model learning devices for problem solving skil in static fluid material that is valid for use. IDEAL problem solving model is expected to make it easier to understand and develop problem solving skil for students. The device consist of a learning implementation plan, student worksheets, and cognitive test. This research and development (R&D) research uses the 4D model. This research is only limited to the development. The results showed that the learning device using the IDEAL problem solving model was declared valid with overall score of the device being 3,50 with very high category. Thus, the IDEAL problem solving is feasible to be used for learning physics on static fluid material.Key Words: Physics Learning Device, IDEAL Problem Solving Model, Static Fluid Material.